Mewujudkan Konsistensi Kebijakan Melalui Pedoman Penyusunan dan Penyelarasan Naskah Akademik - Sujatmiko Sujatmiko; Endah Kartina; Oki Wahju Budijanto; Edy Sumarsono; Maryati Maryati; Tony Yuri Rahmanto; Yudhi Chaerudin; Faris Hasan Fauzi (Jurnal Ilmiah Kebijakan Hukum, 2025)
The preparation and alignment of academic manuscripts is an important process because the results can be the basis for the preparation of policies or laws. However, there are several obstacles in its practice, namely academic texts do not start with legal research or other studies, lack of public participation and neglect of policy initiators to a number of processes in alignment. This paper aims to analyze the urgency of forming and formulating content, guidelines, and procedures for the preparation and alignment of academic manuscripts. This paper uses a qualitative approach through the perspective of policy formulation. The data collection technique was carried out by means of interviews in six provinces, FGDs with relevant stakeholders online and offline, and document studies. The results of the study show that there is a number of urgency in the need to establish guidelines and procedures in the preparation and alignment of academic manuscripts. The content material that can be included in the policy includes definitions or general provisions related to the preparation and alignment of academic manuscripts; limitations on substance or content materials that use academic manuscripts or certificates or explanations; authorities that carry out the process and supervision of the preparation and alignment of academic manuscripts; stages in the preparation and alignment of academic manuscripts; period of time in the process of preparation and alignment academic manuscripts; and the theoretical approach used in the preparation and alignment of academic manuscripts.